The habitus of hygiene: discourses of cleanliness and infection control in nursing work - Brown, Brian; Crawford, Paul; Nerlich, Brigitte; Koteyko, Nelya (Elsevier, 2008)
This paper reports upon a qualitative interview study of 22 matrons, infection control staff and operating theatre staff who were questioned about their working lives and the role they played in the control of healthcare acquired infections such as MRSA virus in the UK. A theoretical framework drawing upon the work of Bourdieu is deployed as his notion of habitus captures the combination of practical work, physical disposition and ways of looking at the world which are displayed in the interview accounts of labour in the healthcare field. Three themes emerged from the analysis: first, the ‘securitization’ of healthcare work, concerned with control, supervision, ‘making sure’ and the management of risk through inspection, audit and the exercise of responsibility; second, the sense of struggle against doctors who were seen to represent a threat to the carefully organized boundaries, through such alleged violations as not washing their hands, wandering between theatre and canteen areas in soiled clothing and thinking the rules did not apply to them; third, in a ‘back to basics’ theme participants emphasised the fundamentals of what they saw to be nursing work and were concerned with cleanliness and practically based training – the habitus of hygiene itself. This was formulated in nostalgic terms with reminiscences about basic training earlier in the participants' careers. The preoccupation with hygiene and its ‘basic’ processes can be seen as a way of managing uncertainty, accumulating a certain kind of symbolic capital and constructing and maintaining boundaries in the healthcare field. It also makes for self-governing, self-exploiting individuals who accrue responsibility to themselves for implementing the ‘habitus of hygiene’.